On seeing-off the first graduate s of Lithuanian school for young mathematicians - Antanas Apynis; Eugenijus Stankus; Juozas Šinkūnas (Lietuvos Matematikos Rinkinys)
The curriculum of Lithuanian school for young mathematicians and its realization is reviewed.